Landscape culture - culturing landscapes. The differentiated construction of landscapes. - (:unkn) unknown (Springer VS, 2015)
Die Beziehung zwischen Raum, Gesellschaft und Kultur in Zeiten zunehmender Multikulturalität sowie der Begriff der Landschaft und seine sozialen und kulturellen Implikationen sind Thema des Sammelbandes der auf den Beiträgen einer internationalen Konferenz beruht.

In this book an international group of authors reflects mechanisms of the cultural and social construction of landscapes. International migration and global exchange are associated with a multitude of different cultural meanings of landscapes. The logics of multi-cultural perceptions and meanings of landscape call for trans-disciplinary research, and for guidance on addressing culturally sensitive issues and inclusion in practical planning.
Keywords: Landschaftsraum; Kulturlandschaft; Strukturwandel; Landschaftsgestaltung; Wahrnehmung; Sozialgeographie; Landschaftsbegriff